(untitled) (Research, Society and Development, 2018)
The food offered to schoolchildren should include quantitative and qualitative aspects for the fulfillment of its purpose. In this context, meals produced in school kitchens must be performed within strictly hygienic sanitary criteria. Therefore, the present study aimed to analyze the good practices related to food production in school feeding and nutrition units in a municipality in the state of Sao Paulo. Data were collected through the application via check list. The study was conducted throughout 2017 in six municipal schools. The evaluated locals had a mean score of 48.51%, being thus categorized within a high sanitary risk. Given this, the schools evaluated did not meet the necessary requirements, putting at risk the food available to the students.